Similarities and Differences in Decision-Making Impairments between Autism Spectrum Disorder and Schizophrenia - Zhang, Long; Tang, Jiulai; Dong, Yi; Ji, Yifu; Tao, Rui; Liang, Zhitu; Chen, Jingsong; Wu, Yun; Wang, Kai (Frontiers in Behavioral Neuroscience, 2015)
Although individuals with autism spectrum disorders (ASD) and schizophrenia (SCH) share overlapping characteristics and may perform similarly on many cognitive tasks, cognitive dysfunctions common to both disorders do not necessarily share the same underlying mechanisms. Decision making is currently a major research interest for both ASD and SCH. The aim of the present study was to make direct comparisons of decision making and disorder-specific underlying neuropsychological mechanisms between the two disorders. Thirty-seven participants with ASD, 46 patients with SCH and 80 healthy controls (HC) were assessed with the Iowa Gambling Task (IGT), which measures decision-making under ambiguity, and the Game of Dice Task (GDT), which measures decision-making under risk. The results revealed that both the ASD and SCH groups had deficits for both the IGT and GDT compared with the HC. More importantly, in the IGT, participants with ASD displayed a preference for deck A, indicating that they had more sensitivity to the magnitude of loss than to the frequency of loss, whereas patients with SCH displayed a preference for deck B, indicating that they showed more sensitivity to the frequency of loss than to the magnitude of loss. In the GDT, the impaired performance might be due to the deficits in executive functions in patients with SCH, whereas the impaired performance might be due to the deficits in feedback processing in participants with ASD. These findings demonstrate that there are similar impairments in decision-making tasks between ASD and SCH; however, these two disorders may have different impairment mechanisms.